Gambaran Jenis Pekerjaan Ayah dan Status Pekerjaan Ibu Terhadap Kejadian Stunting di Puskesmas Seputih Surabaya Lampung Tengah - Kalih, Abigael Ludwina; Sutarto, Sutarto; Suharmanto, Suharmanto; Sangging, Putu Ristyaning Ayu (CV. Jasa Sukses Abadi, 2024)
Stunting refers to short or very short stature based on length or height for age that is less than -2 standard deviations on the WHO growth curve. The World Health Organization (WHO) estimated that 22.2% or 149.2 million children under 5 years old suffered from stunting in 2020. Stunting is caused by two factors: direct and indirect factors.This study aims to examine the relationship between the father's type of occupation and the mother's employment status with the incidence of stunting in the working area of the Seputih Surabaya Public Health Center, Central Lampung. The study employed a cross-sectional design, with a sample of 57 toddlers from the Seputih Surabaya Subdistrict, Central Lampung Regency. The research was conducted from September to November 2024. The sampling technique used proportional random sampling and simple random sampling. This study utilized consent forms containing statements of willingness to participate as respondents, and data collection was conducted using questionnaires. The questionnaire included questions about the father’s type of occupation (e.g., farmer, civil servant, entrepreneur/trader, accountant, livestock farmer, fisherman, employee, teacher, or unemployed) and the mother’s employment status (working or not working). The data were analyzed univariately. The results showed that among toddlers with stunting, the most common type of father's occupation was farming, involving 33 children (58%). Regarding the mother’s employment status, the majority of stunted toddlers had mothers who were not working, accounting for 35 children (61.4%).